1994
DOI: 10.1016/0270-9139(94)90763-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte proliferation and gene expression induced by triiodothyronine in vivo and in vitro

Abstract: Subcutaneous injections of hormone triiodothyronine in rats resulted in peak blood levels at 24 hr with return to baseline by 96 hr. The injections stimulated a liver regeneration response that resembled in timing and in magnitude of DNA synthesis (peak, 24 hr) that induced by 40% hepatic resection. The principal proliferation was of hepatocytes. Although there were some temporal differences from the gene expression of transforming growth factor-a, transforming growth factor-~, and c-Ha-ras that are known to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 15 publications
(18 reference statements)
2
79
0
Order By: Relevance
“…This agent is considered a ''weak'' mitogen in that it causes a much lower level of hepatocyte proliferation than two-thirds PH. 13,14 Our finding of a slower rate of liver repopulation in the first month following T 3 administration compared with two-thirds PH (see Laconi et al 11 ) is consistent with this interpretation. An alternative explanation is that in PH-treated animals, there is an acute loss of hepatocyte mass, whereas in T 3 -treated animals, hepatocyte loss occurs more slowly, and replacement by transplanted cells follows the kinetics of endogenous hepatocyte loss.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This agent is considered a ''weak'' mitogen in that it causes a much lower level of hepatocyte proliferation than two-thirds PH. 13,14 Our finding of a slower rate of liver repopulation in the first month following T 3 administration compared with two-thirds PH (see Laconi et al 11 ) is consistent with this interpretation. An alternative explanation is that in PH-treated animals, there is an acute loss of hepatocyte mass, whereas in T 3 -treated animals, hepatocyte loss occurs more slowly, and replacement by transplanted cells follows the kinetics of endogenous hepatocyte loss.…”
Section: Discussionsupporting
confidence: 78%
“…17 Numerous studies have shown also that T 3 , as well as 9-cis retinoic acid and some peroxisome proliferators, are specific inducers of hepatocyte proliferation in rats. 13,14,[18][19][20] To the best of our knowledge, however, no study published to date has evaluated the role of T 3 in stimulating liver repopulation by transplanted hepatocytes.…”
mentioning
confidence: 99%
“…2A; 29, 39) secondary to T 3 administration involves the expansion of Kupffer cell precursors by means of circulating monocyte recruitment, the differentiation of pre-existing local Kupffer cell precursors into mature macrophages, or both, as result of the action of T 3 as a primary hepatic mitogen in vivo, triggering the process of direct hyperplasia (61,62). Consequently, an enhanced ROS generation at the Kupffer cell level is likely to occur in agreement with the significant 105% increase in the NADPH oxidase-dependent respiratory burst activity assessed in the perfused rat liver upon Figure 2.…”
Section: Kupffer Cell Activity In Hyperthyroid Statementioning
confidence: 99%
“…20 Therefore, for clinical applications of liposome-mediated gene delivery, a non-invasive approach that leads to marked hepatocyte proliferation is required. It has been reported recently that thyroid hormone, specifically T 3 , which is used for the treatment of hypothyroidism, and is well tolerated in a clinical setting, causes a repeatable surge of DNA synthesis in the intact livers of euthyroid rats 21 and can stimulate repopulation of transplanted hepatocytes in rats. 22 Pretreatment with thyroid hormone and keratinocyte growth factor significantly enhanced rat hepatocyte proliferation and enabled retroviral gene transfer through systemic administration.…”
Section: Liposome-mediated Liver Gene Deliverymentioning
confidence: 99%